(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2020)
The religious language is considered to be a variety of the general language with the emphasis on the function it performs within a particular community using it on a daily basis. The Neopentecostal language is one of the examples. It is characteristic of the Neopentecostal community, as its name suggests. Not only the functional grammar but also the sociolinguistic as well as the psycholinguistic dimensions should be taken into account when analyzing the inner discourse. Moreover, when talking about the social behaviour, the reference point ought to be defined properly. In the case of Neopentecostal communities, particular features of their religious practices might be considered the focal point. The principal objective of this article is to analyze the elements of verbal communication unique to the Neopentecostal community members. The analysis will be based on the particular strategies of the communicative grammar developed by Aleksy Awdiejew.